Osteopoikilosis of the axial skeleton and pelvis: A rare cause of back pain - Reddy Ravikanth; Kanagasabai Kamalasekar (Wolters Kluwer Medknow Publications, 2019)
Osteopoikilosis (OPK) is an autosomal dominant and rare skeletal condition characterized by discrete ovoid or round, multiple radiodense lesions scattered predominantly in the appendicular skeleton. On radiographs, bone metastases and sclerotic bone dysplasias may mimic OPK. However, OPK is an incidental diagnosis. OPK is an asymptomatic condition but rarely may present with slight joint pains and effusions. Radionuclide bone scans have the propensity to distinguish OPK from osteoblastic bone metastases. Here, we present a 49-year-old female with chronic backache, and imaging revealed OPK of the axial skeleton and pelvis.